hairy mediates dominant repression in the Drosophila embryo. - Barolo, S.; Levine, M. (The EMBO Journal, 1997)
hairy encodes a bHLH repressor that regulates several developmental processes in Drosophila, including embryonic segmentation and neurogenesis. Segmentation repressors such as Krüppel and knirps have been shown to function over short distances, less than 50-100 bp, to inhibit or quench closely linked upstream activators. This mode of repression permits multiple enhancers to work independently of one another within a modular promoter. Here, we employ a transgenic embryo assay to present evidence that hairy acts as a dominant repressor, which can function over long distances to block multiple enhancers. hairy is shown to repress a heterologous enhancer, the rhomboid NEE, when bound 1 kb from the nearest upstream activator. Moreover, the binding of hairy to a modified NEE leads to the repression of both the NEE and a distantly linked mesoderm-specific enhancer within a synthetic modular promoter. Additional evidence that hairy is distinct from previously characterized embryonic repressors stems from the analysis of the gypsy insulator DNA. This insulator selectively blocks the hairy repressor, but not the linked activators, within a modified NEE. We compare hairy with previously characterized repressors and discuss the consequences of short-range and long-range repression in development.